Investigation of contact edge effects in the channel of planar Gunn diodes - Mindil, Ahmed; Dunn, G. M.; Khalid, Ata; Oxley, C. H. (IEEE, 2019)
The effect of the edge of the channel on the operation of Planar Gunn diodes has been examined using Monte Carlo simulations. High fields at the corner of the anode contact are known to cause impact ionization and consequent electroluminescence, but our simulations show that the Gunn domains are attracted to these corners, perturbing the formation of the domains which can lead to chaotic dynamics within the rest of the channel leading to uneven heating and reduced RF output power. We show how novel shaping of the electrical contacts at the ends of the channel reduces the attraction and restores the domain wave-fronts for good device operation.
Keywords: Planar Gunn diode; Monte Carlo; GaAs; Channel Edge